Fossil plant stomata indicate decreasing atmospheric CO 2 prior to the Eocene–Oligocene boundary - M. Steinthorsdottir; A. S. Porter; A. Holohan; L. Kunzmann; M. Collinson; J. C. McElwain (Climate of the Past, 2016)
A unique stratigraphic sequence of fossil leaves of Eotrigonobalanus furcinervis (extinct trees of the beech family, Fagaceae) from central Germany has been used to derive an atmospheric p CO 2 record with multiple data points spanning the late middle to late Eocene, two sampling levels which may be earliest Oligocene, and two samples from later in the Oligocene. Using the inverse relationship between the density of stomata and p CO 2 , we show that p CO 2 decreased continuously from the late middle to late Eocene, reaching a relatively stable low value before the end of the Eocene. Based on the subsequent records, p CO 2 in parts of the Oligocene was similar to latest Eocene values. These results suggest that a decrease in p CO 2 preceded the large shift in marine oxygen isotope records that characterizes the Eocene–Oligocene transition and that when a certain threshold of p CO 2 change was crossed, the cumulative effects of this and other factors resulted in rapid temperature decline, ice build up on Antarctica and hence a change of climate mode.